The effect of precipitation pH and temperature of Mg/Al Hydrotalcite synthesis on the glucose isomerization - Ayu Ratna Permanasari; Rony Pasonang Sihombing; Cecep Yudha Hidayatullah; Solehudin Al-Ayubi; Rijal Muyasar Fahmi; Muhammad Fadly Wiryawan Kautsar,; Wahyu Wibisono (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
Mg/Al Hydrotalcite as the catalyst in isomerization of glucose into fructose was made by coprecipitation of Mg(NO3)2.6H2O and Al(NO3)3.9H2O. Operating condition of precipitation including the temperature and pH was determined by Response Surface Method (RSM). The catalyst synthesis was carried out in the mole ratio of Mg/Al 3:1 for 18 h and the catalyst was activated by calcination for 3 h at 500°C. Catalyst characterization was done by FTIR, BET, and XRD. The highest mass product of Hydrotalcite Mg/Al 4.52 g, reached at the precipitation conditions of pH 9 and temperature of 45ºC. The catalytic activity of hydrotalcite Mg/Al was tested by the isomerization of Glucose into Fructose. The highest yield and selectivity were 20.14%, 62.40%, respectively. It was reached in pH 9 and 45ºC. While the highest conversion, 53.47%, was achieved in the pH 11.12 with a precipitation temperature of 45ºC. By the RSM analysis, neither the mass of catalyst product nor the catalytic activity from the isomerization (yield, conversion, and selectivity) were affected significantly by the pH and temperature precipitation.